Zircon U–Pb age, Hf isotope and geochemistry of Carboniferous intrusions from the Langshan area, Inner Mongolia: Petrogenesis and tectonic implications. (15th April 2016) - Liu, Min; Zhang, Da; Xiong, Guangqiang; Zhao, Hongtao; Di, Yongjun; Wang, Zhong; Zhou, Zhiguang
Highlights: Intrusions from the Langshan area were emplaced at ca. 338–324 Ma. The generation of these intrusions constrains mantle–crust interaction. The intrusions formed in a continental arc setting. Abstract: Late Paleozoic was a critical period for the tectonic evolution of the northern margin of the Alxa-North China craton, but the evolutionary history is not well constrained. The Carboniferous intrusions in the Langshan area in the western part of the northern margin of the Alxa-North China craton are mainly composed of tonalite, quartz diorite, olivine gabbro and pyroxene peridotite. Zircon LA-ICP-MS U–Pb dating indicates that the Langshan Carboniferous intrusions were emplaced at ca. 338–324 Ma. The quartz diorites are characterized by high amounts of compatible trace elements (Cr, Ni and V) and high Mg# values, which may suggest a significant mantle source. The positive Pb and negative Nb–Ta–Ti anomalies, the variable εHf ( t ) (−6.9 to 2.0) values and the old Hf model ages (1218–1783 Ma) imply some involvement of ancient continental materials in its petrogenesis. The tonalite has relatively high Sr/Y ratios, low Mg#, Yb and Y contents, features of adakite-like rocks, negative ε Hf ( t ) values (−9.8 to −0.1) and older Hf model ages (1344–1953 Ma), which suggest significant involvement of ancient crust materials and mantle-derived basaltic component in its petrogenesis. The high Mg# values, high Cr and Ni contents, and low Zr and Hf contents of the mafic–ultramafic rocks show evidence of a mantle source, and the relatively low zircon ε Hf ( t ) values (−5.9 to 3.2) might point to an enriched mantle. The trace element characteristics indicate the influence of subducted sediments and slab-derived fluids. In the tectonic discrimination diagrams, all the rocks plot in subduction-related environment, such as volcanic arc and continental arc. Considering the regional geology, we suggest that the Carboniferous intrusions in the Langshan area were likely emplaced during the late stage of the southward subduction of the Paleo-Asian Ocean plate, which formed a continental arc along the northern margin of the Alxa-North China craton.